Manufacturing cost model for planar 5 kWel SOFC stacks at Forschungszentrum Jülich. (18th March 2020) - Harboe, S.; Schreiber, A.; Margaritis, N.; Blum, L.; Guillon, O.; Menzler, N.H.
Abstract: A study is performed on the manufacturing costs of planar Jülich Solid Oxide Fuel Cell (SOFC) stacks, based on anode-supported cells (ASC). The manufacturing of two ASC concepts with different design approaches (referred to as standard and light-weight) are evaluated on the basis of stacks that have undergone performance and degradation testing. A bottom-up cost model for 5 kWel is constructed to estimate the costs at production volumes of 1 MWel, 10 MWel and 25 MWel per annum. The direct costs of manufacturing are estimated as 2737–1210 €kWel −1 for the standard design, and 2170–580 €kWel −1 for the light-weight design, depending on production volume. For the evaluated concepts, the material costs are estimated to be dominant over the other factors (at the 25 MWel per annum scale > 65%) which is in accordance with most previous studies. The effect of the different design types on the costs is discussed. The steel components are found to be the most cost-intensive, benefiting the light-weight design. Cost sensitivity analyses to manufacturing parameters, power density and degradation are performed, as well as a theoretical scenarios calculated based on low-cost steel type SS441 replacing the costly Crofer materials and co-sintering replacing sequential sintering. The results are compared to previous studies. Strategies for cost-saving are discussed based on 20 years of experience with stack building and testing in Jülich. Highlights: Material costs identified as main cost-factor in the evaluated SOFC stack designs. As demonstrated, costs can be decreased by applying light-weight design. Improving contacting in light-weight design is promising for further cost reduction. It is predicted that applying low-cost stainless steel with appropriate coating decreases cost.